THE ECO-MAGNETIC TRAIN - Ana-Maria PĂTRĂȘCOIU (Fiabilitate şi Durabilitate)
The present work describes a montage that contains a landscape decoration, an eco system, (trees, grass, water, sand) in which an eco-magnetic toy train, with propulsion, raised from the ground, without friction, at high speed, due to the lack of frictional force. The energy used by the toy train is electrical, which is transformed, based on the phenomenon of electromagnetic interaction, into mechanical energy (the electric motor) The idea is to use this kind of energy in the future to reduce pollution, thus creating a dynamic, stable balance between nature and means of transport, electric motors To illustrate the ecosystem, polystyrene, sand, lichens, cardboard were used, and for the magnetic toy train a copper wire, batteries, magnets were used,